Optimization of Starch Adhesive in Bagasse Charcoal Briquettes - Harmiansyah (Department of Mechanical Engineering, Universitas Andalas, 2026)
The limitations of fossil energy are driving the development of the SDGs as the population and energy needs grow. Briquettes made from agricultural waste, especially bagasse, are a potential solution as an alternative energy source that is renewable, environmentally friendly, and can reduce dependence on fossil fuels while utilizing abundant sugar industry waste. This study aims to analyze the quality of bagasse waste briquettes with variations in the addition of starch flour as an adhesive with formulations (0%, 5%, 10%, and 15%). The manufacturing process includes a press method using a pressurized hydraulic machine to produce briquettes with SNI (01-6235-2000) quality standards. The quality parameters tested include density, moisture content, combustion rate, and drop test. The test results showed significant variation in characteristics between treatments. The SU3 treatment showed the highest density (0.7389 g/cm³) with the highest residual combustion ash (12.47%). The SU4 treatment showed the best physical characteristics with a drop test value of 99.11% and the lowest moisture content (20.98%). In addition, the SU4 treatment also has the second lowest combustion rate with a value of 0.084 gr/min, and the lowest combustion residue (1.7 gr). These findings indicate that the SU4 formulation produces briquettes with the best combination of physical characteristics and combustion efficiency.